Adsorption and immobilization performance of pine-cone pristine and engineered biochars for antimony in aqueous solution and military shooting range soil: An integrated novel approach. (15th January 2023) - Khan, Basit Ahmed; Ahmad, Mahtab; Iqbal, Sajid; Ullah, Fath; Bolan, Nanthi; Solaiman, Zakaria M.; Shafique, Munib Ahmed; Siddique, Kadambot H.M.
Abstract: Antimony (Sb–V), a carcinogenic metalloid, is becoming prevalent in water and soil due to anthropogenic activities. Biochar could be an effective remedy for Sb(V)-contaminated water and soil. In this study, we used pristine and engineered pinecone-derived biochar as an innovative approach for treating Sb(V)-contaminated water and shooting range soil. Biochar was produced from pine–cone waste (pristine biochar) and enriched with Fe and Al salts via saturation (engineered biochar). Adsorption tests in water revealed that iron-modified biochar showed higher adsorption capacity (8.68 mg g −1 ) than that of the pristine biochar (2.49 mg g −1 ) and aluminum-modified biochar (3.40 mg g −1 ). Isotherm and kinetic modeling of the adsorption data suggested that the adsorption process varied from monolayer to multilayer, with chemisorption as the dominant interaction mechanism between Sb(V) and the biochars. The post-adsorption study of iron-modified biochar by Fourier Transform Infrared (FTIR) and X-ray diffraction (XRD) further supported the chemical bonding and outer-sphere complexation of Sb(V) with Fe, N–H, O–H, C–O and CC components. The pristine and iron-modified biochars also successfully immobilized Sb(V) in a shooting range soil, more so in the latter. Subsequent sequential extractions and post-analysis by scanning electron microscopy (SEM), energy dispersive X-ray analysis (EDX), and elemental dot mapping revealed that Sb in the treated soil transformed to a more stable form. It was concluded that iron-modified biochar could act as an efficient material for the adsorption and immobilization of Sb(V) in water and soil, respectively. Graphical abstract: Image 1 Highlights: Production and characterization of pinecone pristine and engineered biochars. Adsorption and immobilization of Sb in water and soil were studied. Adsorption of antimony (Sb) is higher for engineered biochar than pristine. Immobilization of Sb is also higher for engineered biochar than pristine.